ROAD PERFORMANCE ANALYSIS USING PKJI 2014 METHOD (CASE STUDY : TROSOBO-KLETEK ROAD, SIDOARJO DISTRICT) - Aulia Dewi Fatikasari; Nia Dwi Puspitasari (CI-TECH, 2021)
The Trosobo-Kletek Highway is one of the roads that has a high level of vehicle density so that it appears that it has experienced traffic jams several times. This is also coupled with the presence of side barriers such as vehicles in and out. So that the Trosobo-Kletek Highway section often experiences traffic jams that occur not only at certain hours, because on this road section there are many factory areas. The important role of this road resulted in a decrease in the level of service. Based on this, it is necessary to monitor the quality of a road segment based on the level of service. In this study, the PKJI 2014 was used to calculate the road performance. As for some of the data needed such as traffic volume, road geometry, and vehicle speed. The analysis carried out is the calculation of Road capacity, peak hour volume, degree saturation, free flow speed, and level of service index. The results of the research conducted during the four days of the survey and the calculations that have been carried out is level of service in the direction of Surabaya-Mojokerto is E and the direction of Mojokerto-Surabaya is F.